The Binge Eating Scale: Structural Equation Competitive Models, Invariance Measurement Between Sexes, and Relationships With Food Addiction, Impulsivity, Binge Drinking, and Body Mass Index - Escrivá-Martínez, Tamara; Galiana, Laura; Rodríguez-Arias, Marta; Baños, Rosa M. (Frontiers in Psychology, 2019)
Introduction: The Binge Eating Scale (BES) is a widely-used self-report questionnaire to identify compulsive eaters. However, research on the dimensions and psychometric properties of the BES is limited. Objective: The aim of this study was to examine the properties of the Spanish version of the BES. Method: Confirmatory Factor Analyses (CFAs) were carried out to verify the BES factor structure in a sample of Spanish college students (N = 428, 75.7% women; age range = 18–30). An invariance measurement routine was carried out across sexes, the latent means were compared, and estimates of reliability and convergent and discriminant validity were presented. Results: A one-factor model fit the data best and was also equivalent between sexes. The scalar invariance model showed statistically significant differences across sexes, with a higher prevalence in women. Regarding reliability, the results were excellent. Finally, high statistically significant correlations were obtained with other measures of binge eating (BE), food addiction, impulsivity, binge drinking, and body mass index (BMI). Conclusions: The Spanish 16-item BES is a valid and reliable scale to evaluate BE in the youth population.